Solusi Optimal Pencarian Jalur Tercepat Menggunakan Algoritma Dijkstra Untuk Mencari Lokasi Cafe Di Bumiayu - Intan Alifiani; Muhamad Aznar Abdillah; Ilsa Saliha (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2021)
The purpose of this study are (1) to represent the route of café location in Bumiayu in the form of graph, (2) To find a solution from the application of the Dijkstra’s algorithm to find location of café in Bumiayu, and (3) To find the recommended fastest route. The method used in this research is literature study, data collection, problem solving, and drawing conclusions. The results showed that (1) the route of café location in Bumiayu could be represented in the form of a graph, (2) the solution was found the implementation of Dijkstra’s algorithm to find the fastest route for the café location in Bumiayu, and (3) the recommended fastest route was obtained from the starting point (v32) to 14 café locations in Bumiayu (v1,v2,v3,v5,v7,v8,v9,v10,v12,v16,v19,v23,v27,v30). There are 13 café locations that match the recommended fastest route based on the calculation of Dijkstra’s algorithm. The route from starting point (v32) to due café (v9) is one example that Dijkstra’s algorithm does not always choose the smallest weight on each side but chooses the fastest route based on the total distance traveled. There is a discrepancy in the recommended fastest route from starting point (v32) to ratawit (v19). Keywords: Dijkstra, fastest route, optimal solution